Cafeteria Diet Abstinence Induces Depressive Behavior and Disrupts Endocannabinoid Signaling in Dopaminergic Areas: A Preclinical Study - de Ceglia, Marialuisa; Romano, Adele; Di Bonaventura, Maria Vittoria Micioni; Gavito, Ana; Botticelli, Luca; Di Bonaventura, Emanuela Micioni; Friuli, Marzia; Cifani, Carlo; de Fonseca, Fernando Rodríguez; Gaetani, Silvana (Current Neuropharmacology, 2025)
BackgroundAlterations of dopamine (DA) transmission in the brain reward system can be associated with an addictive-like state defined as food addiction (FA), common in obese individuals. Subjects affected by FA experience negative feelings when abstinent from their preferred diet and may develop mood disorders, including depression, sustained by alterations in brain DA pathways.ObjectiveThis study aims to investigate the impact of long-term abstinence from a palatable diet on depressive-like behavior in rats, exploring neurochemical alterations in monoamine and endocannabinoid signaling in DA-enriched brain regions, including ventral tegmental area, dorsolateral striatum, substantia nigra and medial prefrontal cortex.MethodsRats underwent exposure and subsequent abstinence from a palatable cafeteria diet. During abstinence, animals were treated with fatty acid amide hydrolase (FAAH) inhibitor PF-3845 (10 mg/kg, intraperitoneal administration every other day). Lastly, animals were subjected to a forced swimming test, and their brains were dissected and processed for high-performance liquid chromatography measurement of monoamines and western blot analyses of markers of the endocannabinoid machinery.ResultsAfter the withdrawal from the palatable diet, animals showed depressive-like behavior, coupled with significant variations in the concentration of brain monoamines and in the expression of endocannabinoid signalling machinery proteins in cited brain areas. Treatment with PF-3845 exerted an antidepressant-like effect and restored part of the alterations in monoaminergic and endocannabinoid systems.ConclusionOverall, our results suggest that abstinence from a cafeteria diet provokes emotional disturbances linked to neuroadaptive changes in monoamines and endocannabinoid signalling in brain areas partaking to DA transmission that could partially be restored by the enhancement of endocannabinoid signalling through FAAH inhibition.
Keywords: dopamine